A PSYCHOANALYTIC EXAMINATION OF IDENTITY AND DISILLUSIONMENT IN SINDYA BHANOO'S A LIFE OF AMERICA (Contemporary Journal of Social Science Review, 2025)
This paper offers a psychoanalytic look at Sindya Bhanoo’s short story A Life of America highlighting themes of identity, displacement, and emotional suppression. The story follows Chandrasekharan (Chand), an older Indian professor living in America, whose longtime support for Indian graduate students comes under scrutiny, resulting in accusations of exploitation. By closely examining the text, the paper reveals that Chand’s kindness—such as providing housing, emotional help, and cultural connection—might be driven not just by a desire to help others but also by his own unresolved trauma and feelings of loneliness. His complicated relationship with his wife, Raji, adds more layers to the narrative, showing their different views on cultural responsibilities and personal boundaries. The analysis also looks at the wider immigrant experience, gaps between generations, and the emotional toll of unrecognized desires and identity struggles faced by those living in diaspora.